2013
DOI: 10.1117/1.jbo.18.10.106013
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic near-infrared imaging reveals transient phototropic change in retinal rod photoreceptors

Abstract: Abstract. Stiles-Crawford effect (SCE) is exclusively observed in cone photoreceptors, but why the SCE is absent in rod photoreceptors is still a mystery. In this study, we employed dynamic near infrared light imaging to monitor photoreceptor kinetics in freshly isolated frog and mouse retinas stimulated by oblique visible light flashes. It was observed that retinal rods could rapidly (onset: ∼10 ms for frog and 5 ms for mouse; time-to-peak: ∼200 ms for frog and 30 ms for mouse) shift toward the direction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…Transient retinal phototropism (TRP) has been observed in both amphibian (frog) and mammalian (mouse) retinas illuminated by oblique visible light [1]. High-resolution microscopy revealed that the TRP is dominated by rod photoreceptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient retinal phototropism (TRP) has been observed in both amphibian (frog) and mammalian (mouse) retinas illuminated by oblique visible light [1]. High-resolution microscopy revealed that the TRP is dominated by rod photoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…As the ROS movement represents a morphological change in the retina, it is logical to hypothesize that the phototropic response of ROSs is a key component of the light-scattering signal [9], i.e., TRP may also originate from the ROSs. Our previous studies showed that the onset time of the intrinsic optical signal (IOS) precedes the onset time of the electroretinographic (ERG) a-wave, which reflects the hyperpolarization of photoreceptor outer segments (OS) [10,11], and the rod dominant phototropism was suggested to be a primary contributor to the IOS [1,12]. Therefore, we further hypothesized that the onset of TRP occurs earlier than cell hyperpolarization in the phototransduction cascade.…”
Section: Introductionmentioning
confidence: 99%
“…11 These studies also revealed that photoreceptor IOSs had a rapid time course (<4 ms after onset of the light stimulus). 13,28 Transient retinal phototropism was reported to be one factor that generates photoreceptor IOSs, [31][32][33] but the IOS physiological source has not been accurately determined yet. Before pursuing clinical applications, it is necessary to establish the relationship between IOS distortions and eye diseases.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, oblique light stimulation evoked transient retinal phototropism (TRP) has been detected in amphibian (frog) and mammalian (mouse) retinas. 10 High-resolution microscopy of freshly isolated retinas indicated that TRP is predominated by rod photoreceptors. 10 We speculate that the rod-dominated TRP may provide a quick compensation for the light inefficiency of oblique illumination, and the time course of the observed TRP can be too short to be detectable by the psychophysical methods used for traditional SCE studies.…”
Section: Introductionmentioning
confidence: 99%